Sertifikasi Halal dalam Perdagangan Internasional: Analisis Maqāṣid al-syarī‘ah, Rezim Perdagangan Global, dan Strategi Penguatan Industri Halal Indonesia: Halal Certification in International Trade: Analysis of Maqāṣid al-syarī‘ah, Global Trade Regime, and Strategy for Strengthening the Indonesian Halal Industry - Arif Mashuri; Nasrullah bin Sapa (Litera Academica Publishing, 2026)
Halal certification has undergone a fundamental transformation from an instrument of religious obedience to a strategic mechanism in the contemporary international trade system. This article aims to analyze halal certification through the perspective of maqāṣid al-syarī‘ah (the principles of Islamic law) and examine its position within the global trade regime and its implications for strengthening Indonesia's position as a global halal industry hub. This research uses a qualitative method with a literature review approach to Islamic normative sources, contemporary maqāṣid al-syarī‘ah theory, national regulations, and Islamic economics and international trade literature. The results show that halal certification has strong normative legitimacy as an instrument for protecting religion, life, and property, while also functioning as a valid non-tariff technical standard within the global trade framework. Indonesia has strategic opportunities through institutional strengthening, digitalization of halal certification, and integration of national halal logistics. However, the fragmentation of global halal standards, limited human resources, and weak international harmonization remain major challenges. This article offers a new conceptual framework that positions halal certification as an instrument of maqāṣid al-syarī‘ah in international trade policy and halal economic diplomacy.